Development of heat supply systems for structural subdivisions of JSC “Russian Railways” - S. V. Glukhov; А. V. Kovalenko; S. V. Chicherin (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
JSC RZD throughout the last time actively realizes the program of energy saving. Specific power consumption of production activity from the moment of foundation of the company has decreased on 25 % generally due to improvement of electric supply systems. From the moment of the organization of the Central management office for heat and water supply in 2011 active implementation of actions in the stationary heat-and-power engineering, numbering more than two thousand heat sources and about 2000 km of heat networks, has begun. Power strategy of JSC RZD has defined implementation of automated block-type boiler and individual heating unit as the main actions. Available statistics of fuel consumption and heating energy shows that the cost of production of heat from its own sources is lower than acquired from outside. This demonstrates the need to develop its own heat sources, including those on the basis of combined heat and electric energy. The issues of development of industrial hubs needs to be necessarily linked to the development of systems of heat supply of human settlements by incorporating measures into the perspective plan of heat supply, as well as inclusion in the investment program of public utility companies. The analysis of the available plans of heat supply of several cities of Siberia and Far East shows that the boilers of the JSC “Russian Railways” described only in the first Chapter of perspective heating plans, and measures for their modernization are not taken into account in the development of cities. Lack of complex study of options development of heat sources with inclusion in investment programs leads systems of heat supply to decrease in efficiency, makes impossible to return investments due to its inclusion in fare rates for production of heat energy. Authors suggest organizing on the basis of the available structures of JSC RZD an expert group which will be engaged in collecting and processing input data, interacting with municipal authorities and regulating organizations for successful modernization of systems of heat supply from boiler units of JSC RZD. The list of the actions is offered, obligatory for consideration at drafting options of development of industrial hubs, taking into consideration specifics of its work. Results of calculations of implementing optional study of actions for one of heat sources of JSC RZD are shown.